THE INFLUENCE OF SOCIAL MEDIA PROMOTION, CUSTOMER ORIENTATION, AND MENU INNOVATION ON THE BUSINESS SUCCESS OF MEATBALL STALLS IN LHOKSEUMAWE CITY - Miranda; Munandar; Naufal Bachri; Muttaqien (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study examines the influence of social media promotion, customer orientation, and menu innovation on the business success of bakso (meatball) stalls in Lhokseumawe City, Indonesia. A quantitative survey design was employed, involving 80 stall owners selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the aid of SmartPLS software. The results show that social media promotion has a positive but statistically insignificant effect on business success (t = 1.461; p = 0.144), largely because most owners have not yet used social media optimally. In contrast, customer orientation (t = 5.344; p = 0.000) and menu innovation (t = 5.544; p = 0.000) both exert a significant positive effect on business success, with menu innovation emerging as the strongest predictor (path coefficient = 0.578). The model explains 73.0% of the variance in business success (R² = 0.730) and demonstrates strong predictive relevance (Q² = 0.617). These findings imply that the success of small culinary enterprises such as bakso stalls depends more on owners' ability to understand customer needs and to continuously innovate their products than on digital promotion alone.